2021
DOI: 10.1093/pm/pnaa446
|View full text |Cite
|
Sign up to set email alerts
|

The Early Impact of COVID-19 on Chronic Pain: A Cross-Sectional Investigation of a Large Online Sample of Individuals with Chronic Pain in the United States, April to May, 2020

Abstract: Objective Individuals with chronic pain are uniquely challenged by the COVID-19 pandemic, as increased stress may exacerbate chronic pain, and there are new barriers to receiving chronic pain treatment. In light of this, using a large online sample in the United States, we examined 1) the early impact of COVID-19 on pain severity, pain interference, and chronic pain management; and 2) variables associated with perceived changes in pain severity and pain interference. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
80
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(86 citation statements)
references
References 31 publications
6
80
0
Order By: Relevance
“…In the area of chronic pain, several studies have highlighted racial inequities regarding pain assessment and access to analgesia, with racialized persons facing prejudices, stigma, and lack of recognizing of their pain [ 27 , 32 , 75 ]. According to a recent study, Black Americans with chronic pain were particularly at risk of experiencing higher pain levels and disruptions in mood and sleep during the COVID-19 first wave [ 45 ]. By highlighting the specific challenges of belonging to a racial minority with chronic pain during the pandemic, our results contribute to situate their deteriorated pain outcomes within social experiences and systemic barriers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the area of chronic pain, several studies have highlighted racial inequities regarding pain assessment and access to analgesia, with racialized persons facing prejudices, stigma, and lack of recognizing of their pain [ 27 , 32 , 75 ]. According to a recent study, Black Americans with chronic pain were particularly at risk of experiencing higher pain levels and disruptions in mood and sleep during the COVID-19 first wave [ 45 ]. By highlighting the specific challenges of belonging to a racial minority with chronic pain during the pandemic, our results contribute to situate their deteriorated pain outcomes within social experiences and systemic barriers.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that women experienced specific difficulties in accessing their usual pain treatment. In an American study, no differences were found between women and men in terms of changes in pain severity and interference in daily life during the COVID-19 first wave [ 45 ]. However, the authors state that differential impacts will likely appear over time, given the existing literature documenting gendered disparities related to pain [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides its direct impact on public health in the US, the COVID-19 pandemic also has had many subtle and less direct effects. For example, many people with non-COVID health issues have encountered difficulties in obtaining appropriate care for their non-COVID problems, as national health leaders called for hospitals to forgo routine visits as well as screening and elective procedures (Puntillo et al, 2020;Caton et al, 2021;Jacka et al, 2021;Kedia et al, 2021;Linas et al, 2021;Mun et al, 2021;Peckham et al, 2021). The lack of access to care has been especially acute for patients with chronic pain problems and/ or substance use disorders (Jacka et al, 2021;Kedia et al, 2021;Narayan and Balkrishnan, 2021).…”
Section: Impact Of the Covid-19 Pandemic On Supply And Demand For Kratommentioning
confidence: 99%